Clinical and instrumental criteria for the prognosis of the course of hereditary motor-sensory neuropathy type 1A - Govbakh , I.O.; Grechanina , O.Ya.; Tsogoeva , L.M.; Molodan, L.V. (Medicni Perspektivi, 2025)
Hereditary motor-sensory neuropathies (HMSN) are a large group of genetically heterogeneous diseases of the peripheral nerves, characterized by symptoms of progressive polyneuropathy with a predominant lesion of the muscles of the distal parts of extremities. The progressive course of the disease and the lack of effective etiological therapy lead to early disability of patients and significantly reduce the level of their quality of life due to significant limitations in gait and self-care. The study of the relationship between neurophysiological indicators, anamnestic data and clinical and neurological characteristics of patients with HMSN type 1A is important for understanding the pathophysiology of clinical polymorphism, as well as factors affecting the severity and rate of progression of the disease. The aim of the work was to determine clinical and instrumental criteria for predicting the severity of HMSN type 1A. The study included 153 patients with HMSN type 1A. During the study, a comprehensive approach was applied using clinical and anamnestic, clinical and neurological, clinical and genealogical, and electroneuromyographic methods. Conducting a comprehensive assessment of testing data using the following diagnostic scales and questionnaire: "Neuropathy Impairment Score (NIS)", "Neuropathy Disability Score (NDS)", "Medical Research Council Weakness Scale Sum Score (MRC-SS)", "Overall Disability Sum Score (ODSS)", "Bartel's Daily Activity Scale (Bartel Index)", and the "Functional Walking Categories" test allowed us to objectify the criteria for determining the severity of HMSN type 1A and improve the quality of diagnosis of functional disorders due to this pathology. The majority of the examined patients, namely 41.2%, were aged from 36 to 60 years at the time of examination. Early clinical debut of the disease (up to 20 years) in the examined was observed in 65.4% of cases; the average age of clinical debut of the disease was 19.3 years. In the vast majority of patients, namely 43.8%, the duration of the period of clinical manifestation of the disease was more than 10 years. The electroneurophysiological pattern in the vast majority of the examined patients was characteristic of diffuse demyelination and axonal loss of varying degrees; a gross decrease in the SPI was determined in the motor nerves, mainly of the lower extremities. According to the Spearman rank correlation coefficient, a correlation between the amplitude of the M-response and the age of the disease debut, as well as between the amplitude of the M-response and the age at the time of examination; and was absent a high degree of negative correlation between the amplitude of the M-response and the duration of the period of clinical manifestation of the disease was determined. Analysis of the obtained research results allowed us to determine the following clinical, anamnestic and instrumental criteria for the prognosis of the course of HMSN type 1A: 1) low M-response amplitudes from the beginning of clinical debut are a prognostic criterion for an unfavorable prognosis with a severe clinical course and a rapid rate of progression; 2) late clinical debut (after 20 years) is a prognostic criterion for a rapid rate of disease progression; 3) a decrease in M-response amplitudes is a prognostic criterion for the progression of the pathological process and indicates an aggravation of the severity of the disease before the appearance of clinical signs.